Students’ Integration into the Workplace. The Paradigm of Emotional Intelligence in the Context of the European Higher Education Area (EHEA) - del Val Merino, Carlos (Estudios sobre el Mensaje Periodístico, 2013)
The dynamic business environment characterized by the globalization effect has developed new Business management styles that demand new university profiles needed to cover the market demands. This radical change requires a mandatory approach between the real business demands and the new European Higher Education Area (EHEA) framework, where student must become the main protagonists, due to the fact that they will face working situations completely unknown by them. Emotional Intelligence becomes an essential discipline to be adopted by higher education institutions in their curricula to provide students with a comprehensive education which combines academic skills with strictly no cognitive intelligences that will help them to grow personally and professionally.
Keywords: European Higher Education Area (EHEA); University; Emotional Intelligence; Market